Recycling of graphite anode from spent lithium‐ion batteries: Advances and perspectives - Qiao, Yu; Zhao, Huaping; Shen, Yonglong; Li, Liqiang; Rao, Zhonghao; Shao, Guosheng; Lei, Yong (EcoMat (Beijing, China), 2023)
There is growing production for lithium‐ion batteries (LIBs) to satisfy the booming development renewable energy storage systems. Meanwhile, amounts of spent LIBs have been generated and will become more soon. Therefore, the proper disposal of these spent LIBs is of significant importance. Graphite is the dominant anode in most commercial LIBs. This review specifically focuses on the recent advances in the recycling of graphite anode (GA) from spent LIBs. It covers the significance of GA recycling from spent LIBs, the introduction of the GA aging mechanisms in LIBs, the summary of the developed GA recovery strategies, and the highlight of reclaimed GA for potential applications. In addition, the prospect related to the future challenges of GA recycling is given at the end. It is expected that this review will provide practical guidance for researchers engaged in the field of spent LIBs recycling. This review covers the importance of graphite anode (GA) recycling from spent lithium‐ion batteries (LIBs), the introduction of the aging mechanisms of GA in LIBs, the summary of the developed recovery strategies of GA from spent LIBs, and the highlights of applications potentials of the reclaimed GA as well as the prospects related to the challenges of future GA recycling.